Sengketa Kewenangan dalam Proses Likuidasi Boedel Pailit antara Kurator dengan Kejaksaan Republik Indonesia - Andrian, Andrian (JUSTISI, 2023)
The dispute over execution authority between general confiscation in bankruptcy law and criminal confiscation in criminal law is a classic problem that until now has not found a solution because each of these legal dimensions has its own legal certainty. On the criminal law side, criminal confiscation is a natural thing considering the procedural law regulates this matter. Likewise on the side of bankruptcy law, where general confiscation is a juridical consequence of the debtor's bankruptcy determination. This problem then becomes an irony because both general confiscation and criminal confiscation applied in a case are efforts that both uphold the interests of creditors or victims. This study will concentrate on the issue of protecting creditors from the problem of overlapping authorities to liquidate estates in bankruptcy. Both normative legal research approaches and qualitative analytical techniques will be used in this study. It is intended that this research will not only increase readers' understanding but also serve as a legal construction solution for associated parties to address authority conflicts throughout the liquidation process. estate insolvent. Keywords: General Confiscation; Criminal Confiscation; Creditor Protection.